Molecular detection of blaVIM and blaNDM in multidrug-resistant Pseudomonas aeruginosa from cancer and burn patients in Erbil, Iraq - Hamad, Bahra Kakamin; Mahmud, Muayad Ahmed (Frontiers in Microbiology, 2025)
IntroductionPseudomonas aeruginosa is an opportunistic Gram-negative pathogen and a critical-priority organism according to the World Health Organization. Its increasing resistance to multiple antimicrobial classes, including carbapenems, poses a major challenge in treating infections among immunocompromised individuals, particularly burn and cancer patients.MethodsThis cross-sectional study investigated phenotypic resistance profiles, carbapenemase classifications using an advanced expert system, and the molecular prevalence of blaVIM and blaNDM genes in 50 clinical isolates from cancer, burn, and other immunocompromised patients in Erbil, Iraq.ResultsMultidrug resistance and carbapenem resistance were detected in 66.0 and 58.0% of isolates, respectively, with the highest burden among burn patients (93.8%). Carbapenem resistance was significantly associated with prior carbapenem exposure (p = 0.0044) and increased mortality (p = 0.0392). Carbapenemase-producing isolates classified by the advanced expert system exhibited universal multidrug resistance and more than 95% resistance to imipenem and meropenem. Molecular analysis identified blaVIM in 47.5%, blaNDM in 10.0%, and both genes in 30.0% of tested isolates, with blaNDM significantly associated with carbapenem resistance (p = 0.027). Resistance patterns varied by patient group and antibiotic class, with burn isolates demonstrating the highest rates.Discussion/conclusionThese findings highlight the need for enhanced molecular surveillance, infection control, and antimicrobial stewardship in high-risk settings.